The analysis of the oral hygiene habits among Polish children - Patrycja Łanowy; Katarzyna Mocny-Pachońska; Karolina Kowalska; Agata Trzcionka; Marta Tanasiewicz (Journal of Education, Health and Sport, 2019)
Introduction: The frequency of dental caries among Polish children is higher than in surrounding high development countries at comparable latitude. To reduce the prevalence of the carries required is sufficient level knowledge and oral regimen maintaining habits among both - children and their parents. This article is a questionnaire-based analysis of oral hygiene practice among school-aged children. Material and methods: The single-choice survey was performed on 76 children between 7 and 16 years old, living in the Upper Silesia region of Silesian Voivodeship in Poland. Responders have been divided into three groups (group A - 7-9 years old children, group B - 10-12 years old, group C - over 13 years old). Questionnaire for groups A and B contained 14 questions, while one for children from group C - 12. Results: The results of the survey indicate insufficient intentness of children in processes of keeping proper hygiene in the oral cavity and lacking involvement of parents in the control of oral hygiene of children. The overhead translates into in the future for increased caries presence among Polish children.